2009
DOI: 10.1177/000348940911800101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Oropharyngeal pH Probe and a Standard Dual pH Probe for Diagnosis of Laryngopharyngeal Reflux

Abstract: The OP probe reliably documented LPR events when meals and sleep were eliminated and was better tolerated than the standard dual probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 15 publications
1
48
0
5
Order By: Relevance
“…When data retrieved from Dx pH probe are transferred into a computerized system, any desired value can be determined as a baseline pH and relevant calculations can be performed. [3][4][5][6][17][18][19][20] In an investigation performed on 55 asymptomatic volunteers, Gloub et al [5] reported parallelism between data obtained by Dx pH and standard dualprobe monitorization technique. In another study conducted in Emory University (Atlanta, 2007) Dx pH probe was compared to gold standard dual-probe 24-hour and detected mean pH measurements at the end of a 24-hour monitorization period (excl.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…When data retrieved from Dx pH probe are transferred into a computerized system, any desired value can be determined as a baseline pH and relevant calculations can be performed. [3][4][5][6][17][18][19][20] In an investigation performed on 55 asymptomatic volunteers, Gloub et al [5] reported parallelism between data obtained by Dx pH and standard dualprobe monitorization technique. In another study conducted in Emory University (Atlanta, 2007) Dx pH probe was compared to gold standard dual-probe 24-hour and detected mean pH measurements at the end of a 24-hour monitorization period (excl.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, practical algorithms of history taking and differential diagnosis to be used for the diagnosis of LPR are needed. [5,8,10,13,15] In order to be able to evaluate LPR symptoms and their severity Belafsky et al [3] described a reflux finding scoring (RFS) system which interrogated frequently encountered 8 symptoms of LPR. Scores of RFS ranges from 0 to 26 points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis which tested the role of upper probe measurements across 16 studies and concluded it to be a reliable and consistent method worldwide [8]. Recently probes have been designed for more accuracy (four channels) and better tolerance (aerosol detecting pH probes for oropharyngeal use) [9,10].…”
Section: Diagnosingmentioning
confidence: 99%